Yoga Based Management Of Urinary Incontinence And Over Active Bladder; A Literature Review (The Review of Diabetic Studies, 2025)
Background- Urinary incontinence (UI) is a common and upsetting illness that affects women physically, psychologically, and socially. Pelvic floor muscle training (PFMT) and pharmaceutical treatment are examples of conventional therapies that frequently exhibit poor adherence and inconsistent outcomes. Yoga has become popular in recent years as a non-pharmacological, holistic approach to improve quality of life and pelvic floor function. Titaliasana (Butterfly Pose/Baddha Konasana) is one of the yogasana that has drawn attention due to its ability to help manage continence by strengthening and relaxing the pelvic floor muscles.Objective: To evaluate the effect of the yogasana Baddha Konasana (Butterfly Pose), as a mind–body therapeutic intervention, on the management of urinary incontinence and over active bladder.Methods- A systematic literature search was conducted in PubMed, Google Scholar, and other web databases covering studies from 2010–2025. Thirteen eligible studies, including randomized controlled trials, pilot, observational, and descriptive-analytical designs, were reviewed. Studies focusing on yoga-based interventions for UI in adult women were included, while non-yoga, non-English, or retracted studies were excluded.Result- Yoga therapies significantly decreased episodes of urine leakage, strengthened pelvic floor muscles, and improved participants' quality of life across all analyzed trials. Baddha Konasana and Supta Baddha Konasana facilitated better pelvic alignment, relaxation of overactive muscles, and stabilization of the bladder neck. Improved pelvic posture and bladder support were found by imaging-based findings. Yoga practices were safe, feasible, and well accepted across age groups, often yielding results comparable or superior to PFMT.Conclusion- Yoga - especially Titaliasana (Butterfly Pose)—emerges as a promising, safe, and effective complementary approach for managing urinary incontinence in women. By integrating physical, psychological, and neuromuscular benefits, it provides a holistic alternative to conventional therapy. Large-scale, standardized trials are warranted to establish its independent therapeutic efficacy.